Understanding Affordability: The Economics of Housing Markets - Meen, Geoffrey; Whitehead, Christine (Bristol University Press, 2020)
For many younger and lower-income people, housing affordability continues to worsen. Based on the academic research of two distinguished housing economists - and stimulated by working with governments across the world - this wide-ranging book sets out clear theoretical and empirical frameworks to tackle one of today's most important socio-economic issues. Housing unaffordability arises from complex forces and a prerequisite to effective policy is understanding the causes of rising house prices and rents and the interactions between housing, housing finance and the macroeconomy. The authors challenge many of the conventional wisdoms in housing policy and offer innovative recommendations to improve affordability.